2022
DOI: 10.3390/nu14245345
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Intake Inversely Associated with Cardiovascular-Disease Mortality and Interacting with Folate Intake: Findings from the National Health and Nutrition Examination Survey (NHANES) 2005–2016

Abstract: The association between intakes of riboflavin and mortality has not been examined intensively in general populations. In this study, 10,480 adults in the 2005–2016 National Health and Nutrition Examination Survey (NHANES) were followed-up until 2019 for their vital status. Riboflavin and folate were assessed by two-day 24 h recall. The date and cause of death were obtained from the US Mortality Registry. The risks of all-cause mortality and cardiovascular disease (CVD) mortality were investigated using a Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…We found a strong correlation between the healthy Cantonese dietary pattern and intake of vitamin B2 (riboflavin) and vitamin C. Previous studies showed that vitamin B2 was associated with a lower risk of CVD mortality, probably through its beneficial effect on systolic blood pressure. 67,68 Vitamin C was suggested to prevent arteriosclerosis by inhibiting the oxidative modification of low-density lipoprotein cholesterol (LDL-C), thereby reducing the risk of CVD mortality. 69 Moreover, a MR study showed that higher dietary vitamin C intake, but not vitamin C supplement, was associated with a lower risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a strong correlation between the healthy Cantonese dietary pattern and intake of vitamin B2 (riboflavin) and vitamin C. Previous studies showed that vitamin B2 was associated with a lower risk of CVD mortality, probably through its beneficial effect on systolic blood pressure. 67,68 Vitamin C was suggested to prevent arteriosclerosis by inhibiting the oxidative modification of low-density lipoprotein cholesterol (LDL-C), thereby reducing the risk of CVD mortality. 69 Moreover, a MR study showed that higher dietary vitamin C intake, but not vitamin C supplement, was associated with a lower risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We found a strong correlation between the healthy Cantonese dietary pattern and intake of vitamin B2 (riboflavin) and vitamin C. Previous studies showed that vitamin B2 was associated with a lower risk of CVD mortality, probably through its beneficial effect on systolic blood pressure. 67,68 Vitamin C was suggested to prevent arteriosclerosis by inhibiting the oxidative modification of low-density lipoprotein chole-…”
Section: Possible Explanations Based On Nutrientsmentioning
confidence: 99%
“…A study has reported that ribo avin intake lower than the recommended level was related to an elevated risk of CKD stage 3B or above [9]. In the general populations, ribo avin intake was reported to show an inverse relationship with the risk of all-cause mortality [10]. However, in CKD patients, the relationship between ribo avin intake and all-cause mortality has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A study has reported that ribo avin intake lower than the recommended level was associated with an increased risk of CKD stage 3B and above [9]. In general populations, ribo avin intake was reported to be inversely associated with the risk of all-cause mortality [10]. However, the association between ribo avin intake and the risk of all-cause mortality in CKD patients has not been reported.…”
Section: Introductionmentioning
confidence: 99%